Bioavailability of β‐cryptoxanthin is greater from pasteurized orange juice than from fresh oranges – a randomized cross‐over study. Issue 10 (20th July 2015) - Aschoff, Julian K.; Rolke, Christa L.; Breusing, Nicolle; Bosy‐Westphal, Anja; Högel, Josef; Carle, Reinhold; Schweiggert, Ralf M.
<x xml:space="preserve">Abstract</x> Scope Orange fruits and products thereof represent important dietary sources of carotenoids, particularly β‐cryptoxanthin. Since previous studies reported a positive effect of vegetable processing on carotenoid absorption, our objective was to compare the bioavailability of β‐cryptoxanthin from either fresh navel oranges (Citrus sinensis L. Osbeck) or pasteurized orange juice. Methods and results The study was designed as a randomized 2‐way cross‐over study. Twelve volunteers consumed two meals delivering 744 μg of β‐cryptoxanthin from either fresh navel oranges or pasteurized orange juice. Eight blood samples were collected over 9.5 h after test meal consumption and analyzed using HPLC‐DAD. Additionally, carotenoid bioaccessibility was assessed after in vitro digestion of the same test foods. β‐cryptoxanthin bioavailability from pasteurized orange juice was 1.8‐fold higher than from fresh oranges (P = 0.011). Similarly, mean absorption of the non‐dose adjusted carotenoids lutein (P = 0.301), zeaxanthin (P = 0.216), and zeinoxanthin (P = 0.090) were slightly higher from orange juice, although not reaching statistical significance. The in vitro digestion revealed a 5.3‐fold higher bioaccessibility of β‐cryptoxanthin from orange juice. Dietary fiber contents in the test foods were inversely associated with carotenoid bioavailability. Conclusion Orange juice represents a more bioavailable source of β‐cryptoxanthin than fresh oranges.